TEHNIK DASAR PENULISAN KARYA ILMIAH PENDIDIKAN - Rumina, Rumina (ILJ: Islamic Learning Journal, 2024)
The research was carried out starting from the existence of a problem. Problems are "deviations" from what should be and what happens, deviations between plans and implementation, deviations between theory and practice, and deviations between rules and implementation. The problem appears at a certain time and space. Before conducting research, a researcher must understand the rules of writing scientific papers, namely determining the study area in accordance with the study program, breaking the area into sub-regions, the researcher determining whether to study certain figures, the topic must attract the reader's attention, the topic must be The author knows that the topic should not be too technical. Original, Necessary, Scientific, Consistent and objective. The next step is to prepare a research proposal that broadly includes three main questions, namely: What will be researched?, Why researched?, How will research be done? The research design must be made systematically and logically so that it can be used as a guide that is really easy to follow. The research design, which is often called a research proposal, contains at least four main components, namely the problem, theoretical basis and hypothesis submission, research methods, organization and research schedule.